THE JOURNEY TOWARDS EQUALITY IN THE POEM WANITA DAN ZAMAN BY WIWIK ISTARI Y. TARIGAN: ANALYSIS OF LIBERAL FEMINISM NAOMI WOLF - Mutiara, Mutiara; Saguni, Suarni Syam (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to analyze the representation of feminism in the poem Woman and Time by Wiwik Istari Y. Tarigan using the liberal feminism theory approach by Naomi Wolf. The data collection techniques used are reading and note-taking as well as literature review. The research stages with a feminist approach include: (1) carefully and thoroughly reading the poem, (2) analyzing the feminist aspects within the lines of the poem, and (3) interpreting and understanding the poem through a feminist lens. The data source is the poem Woman and Time by Wiwik Istari Y. Tarigan. The findings reveal various forms of feminism, including (1) voicing women’s oppression in the past, (2) expressing women’s inability to freely express themselves, (3) conveying women’s inner struggles against oppression, (4) highlighting the limitations faced by women in Indonesia compared to European countries, (5) showing the transformation of women from the past to the present era with more freedom, (6) questioning and doubting the freedom of modern women, and (7) emphasizing that the struggle for women’s rights continues.